Sistem Pendidikan Islam Dalam Membangun Karakter: Evaluasi Program Ajengan Masuk Sekolah Di Pangandaran - Iman Subasman; Faat Nasyiruddin (Journal on Education, 2024)
The evaluation explored how the Pangandaran local government played a key role in the implementation and development of the programme, and its impact on students' character development. Data analysis from interviews conducted with the regent, MUI chairperson, school principal, religion teacher, students, ajengan aimed to understand the policy and integration of character education values into the school curriculum. This programme is very interesting because it involves ajengan or religious leaders in the learning process, providing a spiritual and moral dimension to education. This research provides insights into the strategies and challenges in running the AMS programme, as well as its contribution to character education in the school environment. The results provide a valuable understanding of the dynamics and effectiveness of local government-initiated character education programmes.